Importance of Character Education for Civil Servants To Instil Pancasila Values (Jurnal Lemhannas RI, 2024)
Purpose: This research examines the critical need for character education for Civil Servants (ASN) in Indonesia, aimed at cultivating the next generation with Pancasila values. Study Design/Methodology/Approach: A literature review method was utilised to examine the conceptual framework of character education, the role of ASN in its implementation, and its impact on the younger generation.Findings: The findings demonstrate that character education for ASN significantly contributes to developing a future generation characterised by integrity, ethics, and a strong commitment to Pancasila values.Originality/Value: This study highlights the importance of prioritising character education among ASN within national education policies to ensure the perpetuation of Pancasila values in future generations
Keywords: Character education; Civil Servants (ASN); Pancasila values; Public service; Indonesia